MethApp4Mob: A Methodological Approach for Mobile Applications Development - Galeano, Iris; Merín, Mauricio; González, Magalí; Cernuzzi, Luca (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2022.20972, 2022)
The aspects of mobile technology have introduced challenges for developers, raising the need to improve the software development methodologies traditionally used. As a result of the analysis of the state of the art, an agile methodological approach for its development is presented, consisting of 8 phases: negotiation, planning, design, implementation and alpha testing, beta testing and feedback analysis, application publication, release and maintenance, promotion, and a series of steps, good practices, principles and tools, to offer mechanisms to accompany and streamline the development process. Some validations were carried out including a exploratory study, seeking to propose a robust methodology but at the same time easy to apply in a company.